2007
DOI: 10.1080/02791072.2007.10400606
|View full text |Cite
|
Sign up to set email alerts
|

Methadone Maintenance Therapy in Residential Therapeutic Conmmunity Settings: Challenges and Promise

Abstract: The therapeutic community (TC) and methadone maintenance treatment (MMT) have individually demonstrated consistent positive outcomes yet rarely have been combined. This article describes how a well-established residential therapeutic community integrated methadone maintenance treatment into its activities. Practical recommendations regarding how to incorporate MMT in a residential program are provided including topics for staff (training, coordination with the methadone service provider agency), patients (educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…83 Over time, the proven benefits of opioid agonist treatment have prompted efforts to integrate these approaches, and some residential treatment programs have revised admission policies and service provision to accommodate evidence-based treatment and patients' preference. [83][84][85] Given the known benefits of opioid agonist treatment, priority should be given to programs and initiatives aimed at strengthening both the opioid agonist and residential treatment systems of care through an integration of evidence-based treatment approaches to opioid use disorder.…”
Section: Residential Treatmentmentioning
confidence: 99%
“…83 Over time, the proven benefits of opioid agonist treatment have prompted efforts to integrate these approaches, and some residential treatment programs have revised admission policies and service provision to accommodate evidence-based treatment and patients' preference. [83][84][85] Given the known benefits of opioid agonist treatment, priority should be given to programs and initiatives aimed at strengthening both the opioid agonist and residential treatment systems of care through an integration of evidence-based treatment approaches to opioid use disorder.…”
Section: Residential Treatmentmentioning
confidence: 99%
“…This is of particular importance as women treated with TCP increasingly may require multiple treatment programs to manage illicit drug use problem. A study at a TC center in the USA indicated that staff training and the provision of professional TCP increased treatment retention and outcomes among clients (11). More studies are suggested in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the TC environment of the treatment program examined in this study may not extend to other TC programs. The TC had years of experience with incorporating methadone patients into the milieu, and the program made modifications to allow TC residents to receive MMT (see Greenberg et al, 2007), thus findings from this study may not extend to TCs that have policies excluding or discouraging methadone maintenance treatment. In addition, our study did not gather information on short-term interruptions of TC treatment (under 14 days), which could overstate the TC retention rates and make the results less generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…The TC has made a number of modifications to accommodate the presence of residents receiving methadone (see Greenberg et al, 2007). For example, the program designates a “methadone counselor,” a TC staff member who plays a vital role in the process of facilitating the residential treatment program in modifying its services to accept and treat MMT patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation